Prevalence of Trichuris trichiura among the children of age under five years (Bangladesh Journal of Zoology, 2015)
A total of 2880 stool samples of children (under 5 years old) were examined during January to June 2006. The rate of infection of Trichuris trichiura was 5.27%. The highest prevalence was 10.18%, among the children of 2-3 years and none (zero) among 0-1 years. The male children (6.11%) were more infected than the female (4.27%). The mixed infection of T. trichiura and Ascaris lumbricoides (26.31%) was higher than the T. trichiura and Giardia sp. (10.52%). The highest rate of infection (6.74%) was found in June and lowest in January (4%).Bangladesh J. Zool. 41(1): 97-103, 2013